Normalisation of Hamiltonian in photogravitational elliptic restricted three body problem with Poynting-Robertson drag - Mishra, Vivek; Ishwar, Bhola (International Journal of Advanced Astronomy, 2015)
In this paper, we have performed first order normalization in the photogravitational elliptic restricted three body problem Â with Poynting-Robertson drag. We suppose that bigger primary as radiating and smaller primary is an oblate spheroid. We have found the Lagrangian and the Hamiltonian of the problem. Then, we have expanded the Lagrangian function in power series of x and y, where (x, y) are the coordinates of the triangular equilibrium points. Using Whittaker (1965) method, we have found that the second order part H2 of the Hamiltonian is transformed into the normal form.